SPring‐8 BL36XU: Synchrotron Radiation X‐Ray‐Based Multi‐Analytical Beamline for Polymer Electrolyte Fuel Cells under Operating Conditions. Issue 7 (25th March 2019) - Uruga, Tomoya; Tada, Mizuki; Sekizawa, Oki; Takagi, Yasumasa; Yokoyama, Toshihiko; Iwasawa, Yasuhiro
Abstract: We designed and constructed a beamline BL36XU at the 8 GeV synchrotron radiation facility SPring‐8 to provide information required for the development of next‐generation polymer electrolyte fuel cells (PEFCs) by clarifying the dynamic aspects of structures and electronic states of cathode catalysts under PEFC operating conditions and in the deterioration processes by accelerated durability test protcols. To investigate the mechanism and degradation process for the cathode electrocatalysis in practical PEFCs, we developed advanced time‐ and spatially‐resolved in‐situ /operando X‐ray absorption fine structure measurement systems and complementary analytical systems (X‐ray emission spectroscopy (XES), X‐ray diffraction (XRD), X‐ray computer tomography (CT) and hard X‐ray photoelectron spectroscopy (HAXPES)) and combined them to develop multi‐analytical systems at BL36XU. Multi‐analytical systems are very powerful for observing spatial‐temporal features of the transient processes occurring in complex systems such as PEFCs. This account describes the design, performance, and research results of the BL36XU and multi‐analytical in‐situ /operando systems. Abstract : This account describes advanced time‐ and spatially‐resolved in‐situ /operando synchrotron radiation X‐ray‐based multi‐analytical systems developed at newly constructed beamline BL36XU to investigate the mechanism and degradation process for the cathode electrocatalysis in practical polymer electrolyte fuel cells (PEFCs).